Incidence and survival rate of women with cervical cancer in the Greater Amsterdam area - Bulk, S (Nature Publishing Group, 2003)
To evaluate the effect of population-based cervical cancer screening on the occurrence of cervical cancer in The Netherlands, we investigated the incidence and survival of cervical cancer registered by a cancer registry in the Greater Amsterdam area. The incidence rate of squamous cell carcinoma decreased significantly from 9.2/100 000 women in 1988 to 5.9/100 000 in 2000 (P<0.001). The incidence rate of adenocarcinomas remained stable. After adjustment for age, stage and lymph node involvement, the relative risk of death was 1.6 times higher for patients with adenocarcinomas than for patients with squamous cell carcinoma (95% CI 1.2–2.1). The decreased survival was related to histological type, as the effect remained significant after correction for confounding factors. Over time, the prognosis of women with squamous cell carcinoma improved significantly. No significant change was observed for women diagnosed with adenocarcinoma. These results suggest that the screening programme in The Netherlands as executed in the Greater Amsterdam area is associated with a decreased incidence and increased survival of patients with squamous cell carcinoma, but fails to detect (pre)malignant lesions of adenocarcinoma. Since more than 92% of adenocarcinomas and its precursors contain high-risk HPV, adding HPV testing to cytologic screening might improve the present screening programme in detecting adenocarcinoma and its precursor lesions.